Assessing financial vulnerability in partial dollarized economies - Castro, Juan Francisco (2004)
The reduction of macroeconomic vulnerability in emerging markets is at the core of the research agenda.Liability dollarization plays a vital role and its implications have been addressed in the literature via “financial accelerator” mechanism. If we asses vulnerability in terms of the evolution of investment, we claim that, in absence of an asset price channel, departures from a pure float will mitigate vulnerability and improve welfare. Conversely, with an active asset price channel a tighter exchange rate policy will have marginal effects on welfare and vulnerability when compared to that associated to a reduction in liability dollarization.